Gene expression profiling of in vitro cultured macrophages after exposure to the respiratory sensitizer hexamethylene diisocyanate - Verstraelen, S.; Wens, B.; Hooyberghs, J.; Nelissen, I.; Witters, H.; Schoeters, G.; Cauwenberge, P. Van; Heuvel, R. Van Den (Toxicology in vitro, 2008)
Occupational exposure to chemicals is one of the main causes of respiratory allergy and asthma. Identification of chemicals that trigger allergic asthma is difficult as underlying processes and specific markers have not yet been clearly defined. Moreover, adequate classification of the respiratory toxicity of chemicals is hampered due to the lack of validated in vivo and in vitro test methods. The study of differential gene expression profiles in appropriate human in vitro cell systems is a promising approach to identify selective markers for respiratory allergy. As alveolar macrophages display important immunological and inflammatory properties in response to foreign substances in the lung, we aimed at gaining more insight in changes of human macrophages transcriptome and to identify selective genetic markers for respiratory sensitization in response to hexamethylene diisocyanate (HDI). In vitro cultures of human THP-1 cells were differentiated into macrophages and exposed to 55μg/ml HDI for 6 and 10h. Using human oligonucleotide microarrays, changes were observed in the expression of genes that are involved in diverse biological and molecular processes, including detoxification, oxidative stress, cytokine signaling, and apoptosis, which can lead to the development of asthma. These genes are possible markers for respiratory sensitization caused by isocyanates.